The Acquisition Of Speaking Skills For Students Based On The Behaviorism And Cognitivism Theories/ Ø§ÙƒØªØ³Ø§Ø¨ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ø¶ÙˆØ¡ Ø§Ù„Ù†Ø¸Ø±ÙŠØ© Ø§Ù„Ø³Ù„ÙˆÙƒÙŠØ© ÙˆØ§Ù„Ù…Ø¹Ø±ÙÙŠØ© - Gunawan, Gunawan; Ainin, Moh; Bahruddin, Uril (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study was to reveal the acquisition situation and atmosphere of the speaking skills for Students of KMI Pondok Modern Gontor Ponorogo in the views of the Behaviorism and Cognitivism, the factors influencing the acquisition process of the speaking skills, the linguistics problems in the acquisition process of the speaking skills and the resolutions. This research applied a case study using a descriptive qualitative approach. The data was collected using active participant observation, passive non-participant observation, interviews, and documentaries methods. The Miles Huberman model was then used to analyze the data. The results of the research showed that, first, the situations in the speaking skills acquisition include the language instructional classes situation, the islamic studies instructional classes situation, and the situation of using the language in the extra-curricular and everyday life activities. In those situations, students interactively combined the use both behaviorism and cognitivism theories, although the implementation of behaviorism priciples is more dominant. Moreover, the implementation of both theories was highly supported by the language atmospheres in the classrooms and outside the classrooms, as well as the discipline enforcement in the language implementation. Second, the factors influencing the speaking skills acquisition process among others were the area and situation diversities for doing simulation (practice), imitation and repetitions, the availability of many areas and situations for practicing and building the habit, the presence of a mentor among students, language atmosphere in the classroom, language atmosphere outside the classrooms,Â the presence of language role models, feedback and reinforcement, the implementation of discipline, court and monitoring board committee, motivation and self-confidence. Third, the linguistic problems in the acquisition process of studentsâ€™ speaking skills among others were the phonemic system, word arabization, changes in the words meaning, mistakes in the language structure, the use of Indonesian particle and the occurance of local dialect. The resolutions that had been taken by the institution (the boarding school of Gontor) to deal with those problems were correcting the speaking errors, providing language training for the board committee, delivering good language style, providing speaking model, practicing the pronunciation, teaching grammar for middle and upper level students, and giving harder punishment for those who intentionally offended the language practice regulation.